2012
DOI: 10.1007/s10856-012-4676-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and in vitro evaluation of bacterial cellulose membranes functionalized with osteogenic growth peptide for bone tissue engineering

Abstract: The aim of this study was to characterize the physicochemical properties of bacterial cellulose (BC) membranes functionalized with osteogenic growth peptide (OGP) and its C-terminal pentapeptide OGP[10-14], and to evaluate in vitro osteoinductive potential in early osteogenesis, besides, to evaluate cytotoxic, genotoxic and/or mutagenic effects. Peptide incorporation into the BC membranes did not change the morphology of BC nanofibers and BC crystallinity pattern. The characterization was complemented by Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 52 publications
4
71
1
Order By: Relevance
“…The cytotoxicity potential of pure BC was already evaluated by Saska et al, 52 which demonstrated absence of in vitro cytotoxicity effects of BC membranes. In the present study, cytotoxicity assay demonstrated that BC-ClAlPc membrane was non-cytotoxic in CHO-K1 cells.…”
Section: Photophysical Characterizationmentioning
confidence: 99%
“…The cytotoxicity potential of pure BC was already evaluated by Saska et al, 52 which demonstrated absence of in vitro cytotoxicity effects of BC membranes. In the present study, cytotoxicity assay demonstrated that BC-ClAlPc membrane was non-cytotoxic in CHO-K1 cells.…”
Section: Photophysical Characterizationmentioning
confidence: 99%
“…BC has been proposed for application in tissue engineering as a scaffold for cartilage [66,67], bone repair [68][69][70][71], vascular grafts [64,[72][73][74][75] and neural repair [75][76][77][78], or as a barrier membrane for guided bone regeneration [57,58,60,70,71,79]. In addition several composite materials have been developed with the purpose of rendering BC bioactive such as hydroxyapatite (HA) [79][80][81][82][83][84][85], collagen [70,[86][87][88], gelatin [85,89], peptides [71,90] and some polymers such as chitosan [35], silk [90][91][92][93], polyhydroxybutyrate [94,95] and poly(2-hydroxyethyl methacrylate) [96].…”
Section: Scaffoldmentioning
confidence: 99%
“…In addition several composite materials have been developed with the purpose of rendering BC bioactive such as hydroxyapatite (HA) [79][80][81][82][83][84][85], collagen [70,[86][87][88], gelatin [85,89], peptides [71,90] and some polymers such as chitosan [35], silk [90][91][92][93], polyhydroxybutyrate [94,95] and poly(2-hydroxyethyl methacrylate) [96]. The incorporation in BC of antimicrobial agents such as propolis, chitosan, potassium sorbate and silver nanoparticles has been already mentioned.…”
Section: Scaffoldmentioning
confidence: 99%
See 2 more Smart Citations